Beyond LEO Human Health Issues for Deep Space Exploration - Reynolds, Robert J. (IntechOpen, 2020)
This book presents a small sample of the physiological changes and human health risks that have been observed in low Earth orbit, and that will undoubtedly be magnified with extended exploration operations to deep space. The book presents the evidence to date and offers a glimpse at what will be needed to take humanity further into deep space than ever before.